2014
DOI: 10.1016/j.meegid.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of serotype A foot-and-mouth disease viruses in Kenya from 1964 to 2013; implications for control strategies in eastern Africa

Abstract: Serotype A is the most genetically and antigenically diverse of the foot-and-mouth disease virus (FMDV) serotypes. Records of its occurrence in Kenya date back to 1952 and the antigenic diversity of the outbreak viruses in this region is reflected by the current use of two different vaccine strains (K5/1980 and K35/1980) and previous use of two other strains (K18/66 and K179/71). This study aimed at enhancing the understanding of the patterns of genetic variation of serotype A FMDV in Kenya. The complete VP1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
4
17
0
Order By: Relevance
“…The use of conventional RT-PCR is confirmatory diagnostic procedure in genotyping of FMDV strains using typespecific primers [28]. These results were consistent with Wekesa et al, [29] who reported that the most outbreaks of FMDV were caused by serotype O followed in frequency by serotype A which is endemic in many developing African and Asian countries. These results were supported by Mohammed et al [30] who detected recent FMDV strains of serotypes, O and SAT-2 in Egypt using primers specific for vp 1 and 3D genes.…”
Section: Discussionsupporting
confidence: 86%
“…The use of conventional RT-PCR is confirmatory diagnostic procedure in genotyping of FMDV strains using typespecific primers [28]. These results were consistent with Wekesa et al, [29] who reported that the most outbreaks of FMDV were caused by serotype O followed in frequency by serotype A which is endemic in many developing African and Asian countries. These results were supported by Mohammed et al [30] who detected recent FMDV strains of serotypes, O and SAT-2 in Egypt using primers specific for vp 1 and 3D genes.…”
Section: Discussionsupporting
confidence: 86%
“…The need for repeated vaccination and the lack of sufficient quality vaccine of the appropriate strain composition slows the progression of vaccine‐based FMD control programs. In recent years, the genetic diversity and co‐circulation of multiple FMDV serotypes (O, A, SAT 1, SAT 2) (Ayebazibwe, Mwiine, Tjørnehøj, et al, ; Mwiine et al, ; Namatovu, Belsham, et al, ; Namatovu, Tjørnehøj, et al, ; Wekesa et al, , ) and SAT 3 in Eastern Africa has become evident (Dhikusooka et al, ). This study aimed to determine the seroprevalence of FMDV across eastern, central, western and northern regions of Uganda, as well as to identify the serotypes and phylogenetic characteristics of FMDV circulating in this country.…”
Section: Discussionmentioning
confidence: 99%
“…These sequences are described in depth by Omondi et al (). National Center for Biotechnology Information (NCBI) GenBank blast searches retrieved one additional buffalo sequence from Kenya for each serotype (Wekesa et al, ). Furthermore, using GenBank searches, we retrieved all published SAT1 ( n = 406) and SAT2 ( n = 694) sequences collected from Africa and the Middle East between 1975 and 2015.…”
Section: Methodsmentioning
confidence: 99%
“…FMDV genomic RNA comprises~8,500 sites and encodes four structural proteins (VP1–4) (Domingo, Baranowski, Escarmis, & Sobrino, ). The VP1 gene segment (of ~639 nucleotides) is the most genetically variable of the four gene segments, with marked mutation rates of up to 10 −2 to 10 −3 substitutions per site per year (Sangula et al, ), and has frequently been used for molecular epidemiological analyses (Brito et al, ; Pedersen et al, ; Sangula et al, ; Wekesa et al, ).…”
Section: Introductionmentioning
confidence: 99%